(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
What role does directing play in the process of contemporary artistic creation? To what extent does the production context affect and condition directing procedures? What constitutes the field of theater directing, in terms of ways of doing things, in Brazil? These are some of the questions that are discussed in this text: an interview with director Christiane Jatahy, conducted in April 2024, remotely while she was finalizing her production of Hamlet, scheduled to open in Brussels later that year.